Teacher Commitment to Teaching and Its Impact on Student Academic Performance in Indonesian Language Subject - Werang, Basilius Redan; Suarjana, I Made; Fajrianti, Wiwik; Asaloei, Sandra Ingried (Jurnal Pendidikan Progresif, 2022)
Objective: A high-quality education requires a high teachers' teaching commitment. The purpose of this study was to assess the impact of teacher teaching commitment on the academic performance in Indonesian language subject among the state junior high school students in Merauke, Indonesia. Methods: The data on teacher teaching commitment were obtained from 309 junior high school students, while the data on the state junior high school students' academic performance were obtained from the surveyed students’ academic records. The data were analyzed statistically using SPSS version 21. Findings: Statistical analysis revealed that teacher teaching commitment has a positive influence on the academic performance in Indonesian language subject among the state junior high school students in Merauke, Indonesia, as the R2 coefficient value was found to be .727 and the Sig. F Change value was .000. Conclusion: Based on the result of statistical analysis, the study gives a deeper knowledge of the impact of teachers’ commitment to teaching on the academic performance in Indonesia language subject among the state junior high school students in Merauke, Indonesia.Keywords: academic performance, students, teachers, teaching commitment.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202234